OPTIMALISASI MODUL SEBAGAI KONSELING PREVENTIF KEKERASAN SEKSUAL PADA SANTRI PEREMPUAN - Firda Rodliyah (Jurnal Harkat : Media Komunikasi Gender, 2023)
Abstract. This study describes the process of preventive counseling through the use of modules for female santri at Pondok Pesantren Nurul Jadid Sejati. It is known that sexual violence can occur anytime and anywhere, including pondok pesantren. This is corroborated by data released by any mediums that in recent years there have been many cases of sexual violence that have occurred in pondok pesantren. Based on this, one way to prevent it is through individual knowledge about their reproductive organs and health. In the research process, I developed a product in the form of an Islamic reproductive health module which was packaged according to the circumstances and needs of the students. Using the RnD (Research and Development) research method, I want to find out the changes in the knowledge of the santri both before and after preventive reproductive health counseling through a product in the form of a module. Sources of data in this study were obtained from interviews with asatidz and preventive counseling to female santri.. In addition, there are also various sources of literature data from news, location documents, journals, and books. The results of this study were that there was a significant change from before the action stage 80% did not understand knowledge about reproductive health, so that it changed to 88.9% of students who understood well how the module and the material in it worked as provisions in daily life and maintaining themselves from the potential for sexual violence anywhere and anytime. Abstrak. Penelitian ini memaparkan proses konseling prevetif melalui penggunaan modul pada para santri perempuan Pondok Pesantren Nurul Jadid Sejati. Diketahui bahwa kekerasan seksual bisa terjadi kapanpun dan dimanapun, termasuk halnya pesantren. Hal ini dikuatkan dengan data yang dikupas oleh berbagai media bahwa beberapa tahun terakhir telah banyak kasus kekerasan seksual yang terjadi di Pesantren. Berdasarkan hal tersebut, salah satu cara untuk mencegahnya adalah melalui pengetahuan individu tentang organ dan kesehatan reproduksinya. Pada proses penelitian, Saya mengembangkan sebuah produk berupa modul kesehatan reproduksi Islam yang dikemas menyesuaikan keadaan dan kebutuhan para santri. Dengan menggunakan metode penelitian RnD (Research and Development), saya ingin mengetahui perubahan pengetahuan para santri baik sebelum dan sesudah tindakan konseling preventif kesehatan reproduksi melalui produk berupa modul. Sumber data dalam penelitian ini sendiri didapatkan dari wawancara kepada para asatidz dan tindak konseling preventif kepada santri perempuan. Selain itu, juga terdapat berbagai sumber data literatur baik dari berita, dokumen lokasi, jurnal, maupun buku. Hasil dari penelitian ini adalah terdapat perubahan signifikan dari sebelum adanya action staget 80% tidak memahami pengetahuan perihal kesehatan reproduksi, hingga berubah menjadi 88,9% santri telah memahami dengan baik bagaimana kerja modul serta materi di dalamnya sebagai bekal dalam kehidupan sehari-hari dan menjaga dirinya dari potensi kekerasan seksual dimanapun dan kapanpun.